Analysis of The Influence of Customer Experience on Culinary Tourism in M Bloc Space - Angela graziela; Dewantara, Yudhiet Fajar (Sadar Wisata: Jurnal Pariwisata, 2024)
The culinary industry in Indonesia has experienced substantial growth, transforming from a basic necessity into a vibrant lifestyle sector. This study examines M Bloc Space in Jakarta, a notable culinary tourism destination renowned for its diverse food offerings and creative ambiance. Employing a quantitative method and Partial Least Square (PLS) analysis, the research investigates factors influencing customer satisfaction, trust, and revisit intentions among 150 visitors. Findings reveal that customer experience significantly boosts satisfaction and revisit intentions, although its direct impact on trust is not significant, implying trust may be shaped by other factors. High customer satisfaction enhances trust, and both satisfaction and trust are vital for encouraging revisit intentions. The study concludes that exceptional customer experiences and high satisfaction levels are crucial for building trust and fostering repeat visits. M Bloc Space's success underscores the importance of understanding and leveraging customer dynamics to enhance the attractiveness of culinary tourism destinations. With the right marketing strategies and continuous innovation, this place has managed to attract a wide range of audiences, from young people to families, as well as local and international tourists.